Unexpected significance of magnesium ion in the coupling effect of mixed divalent cations on polysaccharide membrane fouling - Meng, Shujuan; Wang, Rui; Yang, Linyan; Chen, Miao; Li, Qinfen; Zhang, Meng (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Cations can regulate the aggregation of polysaccharide chains to affect fouling.•The gel layer homogeneity and permeability are mainly related to the TEP type.•Amorphous-TEP form a compact fouling layer with high filtration resistance.•Particulate-TEP form a porous gel layer, pre-filtrate foulants and alleviate fouling.•The resistance of fouling layer to cleaning is also subject to the Ca2+/Mg2+ ratio. Divalent cations and organics are two main types of foulants in feed water to the membrane processes and cations often bind to organic foulants which significantly affects fouling. Extensive efforts have been devoted to exploring the influence of single cation on organic fouling while there are diverse cations in the feed. Thus, it is essential to understand the coupling influence of different divalent cations on fouling development. In this study, sodium alginate was chosen as a model foulant to investigate the effect of different Ca2+/Mg2+ ratios on its fouling behavior. Filtration performances, the quantity and morphology of transparent exopolymer particles (TEP) derived from alginate were analyzed along with the morphology and structure of corresponding fouling layers. TEP measurements reveal that the Ca2+/Mg2+ ratio is crucial in the characteristics of TEP, which further determines the structure of the fouling layer. At a low Ca2+/Mg2+ ratio, the TEP are amorphous-TEP (a-TEP) with small and unconsolidated structure which forms a fouling layer under pressure with high hydraulic resistance. In contrast, interactions between polysaccharides at high Ca2+/Mg2+ ratio are much stronger and result in large and tight particulate-TEP (p-TEP). Such p-TEP lead to a fouling layer with high porosity and low hydraulic resistance. The role of Mg2+ in polysaccharide fouling is more important than expected because it promotes the formation of a-TEP, which show a high fouling potential at high levels because more dense gel layer forms. This study suggests that the morphology and structure of TEP play crucial roles in polysaccharide fouling propensities. A-TEP at high levels needs more attention to ensure the successful operation of membrane systems in future work.